Kesawan Region: The Old City of Medan From the Past to the 21st Century As Historical Tourism - Cynthia C.A Sitorus*; Iren Sintiya Pelawi; Hery Junianto S Marbun; Tappil Rambe; Rosmaida Sinaga; Najuah Najuah (Universitas Syiah Kuala, 2023)
Medan City is the capital of North Sumatra Province which of course is on the island of Sumatra. The city of Medan as the third largest metropolitan capital in Indonesia also has a long history that started from a village whose initial opening was the size of a field opened by Guru Patimpus Pelawi who came from the Karo ethnicity who until now is known as the founder of the city of Medan. And in subsequent developments this city was dominated by ethnic Malays since the founding of the Deli Sultanate by Gocah Pahlawan who came from the Aceh Sultanate which made Medan until now still known as Tanah Deli or Medan Deli and at a time not much different, a person from the Colonial nation (Dutch ) named Jacob Nienhyus around the 1860s established plantations especially for tobacco commodities which almost covered the city of Medan so that in the term Medan Putri was known or the producer of Deli Tobacco which was famous to foreign countries at that time. With the area of the plantation, of course, workers were needed, so Nienhyus brought in a large number of coolies from ethnic Chinese and of course the coolies needed a place to live. Until then the Kesawan area that we know today was formerly a Malay village which was then a result of the large influx of Chinese letnics making this area subsequently dominated by ethnic Chinese who then built houses in the form of shops and started businesses by trading and several administrative office buildings Colonialism also exists in the area as we can see to this day, both the buildings that still function as housing complexes and the remains of the ruins of the building's foundations. And until now this area has become one of the historic iconic locations in the city of Medan, especially at night decorated with various street lights that illuminate this area to just relax and even become a background in documentation for selfies to become a culinary center.